2022
DOI: 10.1136/bmjopen-2021-059017
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the poststroke experiences and unmet needs of South Asian communities in high-income countries: a scoping review protocol

Abstract: IntroductionSouth Asian groups experience a higher burden of stroke and poorer functional outcomes after stroke than their White counterparts. However, within the stroke literature, there has been little focus on the unique poststroke needs of the South Asian community and opportunities for community-based services to address these needs.Research questionWhat is the current knowledge base related to the experiences and needs, including unmet needs of people living with stroke and their caregivers from South As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…Existing reviews describe some of the experiences and health needs of older persons during conflict situations; however, these often focus on specific health outcomes (e.g., mental health 15 ), specific geographical areas, 16 or solely on low‐and middle‐income countries 17 . These reviews have not tended to focus on the unmet needs of older persons and their caregivers, during conflict situations 9,18 . While recent commentaries have included some data about older persons during conflict situations, 8,9 there currently exists no comprehensive review of the available evidence to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing reviews describe some of the experiences and health needs of older persons during conflict situations; however, these often focus on specific health outcomes (e.g., mental health 15 ), specific geographical areas, 16 or solely on low‐and middle‐income countries 17 . These reviews have not tended to focus on the unmet needs of older persons and their caregivers, during conflict situations 9,18 . While recent commentaries have included some data about older persons during conflict situations, 8,9 there currently exists no comprehensive review of the available evidence to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…17 These reviews have not tended to focus on the unmet needs of older persons and their caregivers, during conflict situations. 9,18 While recent commentaries have included some data about older persons during conflict situations, 8,9 there currently exists no comprehensive review of the available evidence to the best of our knowledge. Thus, the objectives of this scoping review are to (1) identify, categorize, and summarize the existing knowledge about the experiences of older persons and their caregivers during conflict situations; (2) identify the support needs of older persons and their caregivers, and; (3) identify gaps in the literature and understanding that may inform future research.…”
Section: Introductionmentioning
confidence: 99%
“…The needs of stroke survivors can be influenced by various sociocultural factors. Existing studies or reviews reported unmet care needs in stroke survivors from different countries 9–11. However, they did not synthesise all the needs met or unmet and did not map the needs based on the Supportive Care Needs Framework (SCNF) for this population.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies or reviews reported unmet care needs in stroke survivors from different countries. [9][10][11] However, they did not synthesise all the needs met or unmet and did not map the needs based on the Supportive Care Needs Framework (SCNF) for this population. Moreover, fewer evidence-based tools were reported to assess the SCNs of stroke survivors.…”
Section: Introductionmentioning
confidence: 99%